Antennal sensilla morphology of Theocolax elegans (Westwood) (Hymenoptera: Pteromalidae), a larval parasitoid of the maize weevil, Sitophilus zeamais (Motschulsky) (Coleoptera: Curculionidae) - Namikawa, Supawan Kongjaroen; Amornsak, Weerawan (Agriculture and Natural Resources, 2016)
The antennal sensilla of Theocolax elegans (Westwood) (Hymenoptera: Pteromalidae), a larval parasitoid of the maize weevil, Sitophilus zeamais Motschulsky (Coleoptera: Curculionidae) were investigated using scanning electron microscopy. The antennal sensilla of female and male wasps appeared similar in shape and types. Antennal sensilla in female and male T. elegans were classified into four groups: basiconic capitate peg sensilla, chaetica sensilla (types 1-5), placoid sensilla and trichoid sensilla. Chaetica sensilla type 5 were found only on the female antenna. These four groups of antennal sensilla probably function as proprioceptors, hygro- and thermo- mechanoreceptors or contact chemoreceptors. The receptors are involved in host examination, host discrimination, host recognition and host location by female and male T. elegans.